Top predators negate the effect of mesopredators on prey physiology. (25th April 2016) - Palacios, Maria M.; Killen, Shaun S.; Nadler, Lauren E.; White, James R.; McCormick, Mark I.
Summary: Predation theory and empirical evidence suggest that top predators benefit the survival of resource prey through the suppression of mesopredators. However, whether such behavioural suppression can also affect the physiology of resource prey has yet to be examined. Using a three‐tier reef fish food web and intermittent‐flow respirometry, our study examined changes in the metabolic rate of resource prey exposed to combinations of mesopredator and top predator cues. Under experimental conditions, the mesopredator (dottyback, Pseudochromis fuscus ) continuously foraged and attacked resource prey (juveniles of the damselfish Pomacentrus amboinensis ) triggering an increase in prey O2 uptake by 38 ± 12·9% (mean ± SE). The visual stimulus of a top predator (coral trout, Plectropomus leopardus ) restricted the foraging activity of the mesopredator, indirectly allowing resource prey to minimize stress and maintain routine O2 uptake. Although not as strong as the effect of the top predator, the sight of a large non‐predator species (thicklip wrasse, Hemigymnus melapterus ) also reduced the impact of the mesopredator on prey metabolic rate. We conclude that lower trophic‐level species can benefit physiologically from the presence of top predators through the behavioural suppression that top predators impose on mesopredators. By minimizing the energy spent on mesopredator avoidance and the associated stress response to mesopredator attacks, prey may be able to invest more energy in foraging and growth, highlighting the importance of the indirect, non‐consumptive effects of top predators in marine food webs. Abstract : This study provides novel empirical evidence of a cascade of indirect effects in which low trophic‐level species can benefit physiologically from the presence of top‐predators, through the behavioural suppression imposed on mesopredators. Linking behavioural and physiological effects on predation risk can help unravel the mechanisms by which top‐predators influence natural ecosystems.